2012
DOI: 10.3945/ajcn.112.034256
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 supplementation (4000 IU/d for 1 y) eliminates differences in circulating 25-hydroxyvitamin D between African American and white men

Abstract: The results of this clinical study show the feasibility and efficacy of this approach in the elimination of hypovitaminosis D, which is a widespread health disparity among African Americans. This trial was registered at clinicaltrials.gov as NCT01045109.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…These include associations with CDAI, muscle function, fatigue, QoL, maintenance of epithelial barrier function, decreased hospitalisations, reduced risk of surgery and cancer. In terms of dosage required to achieve these levels 20-25μg (800-1000 IU)/d vitamin D 3 appears sufficient to achieve a serum level of 50 nmol/l, and between 25 and 100μg (1000 and 4000 IU)/d to bring levels beyond 75 nmol/l (on average 50μg (2000 IU)/d is required for this purpose (114)(115)(116)(117)(118)(119)(120)(121)(122)(123) ). In the present study of Crohn's disease patients, we found that 50μg (2000 IU)/d increased mean 25(OH)D levels to 91·6 (95% CI 75·5, 107·6) nmol/l over winter months, which was significantly higher than levels in the placebo group 40·4 (95% CI 30·4, 50·4) nmol/l (P < 0·001) (34) .…”
Section: Resultsmentioning
confidence: 99%
“…These include associations with CDAI, muscle function, fatigue, QoL, maintenance of epithelial barrier function, decreased hospitalisations, reduced risk of surgery and cancer. In terms of dosage required to achieve these levels 20-25μg (800-1000 IU)/d vitamin D 3 appears sufficient to achieve a serum level of 50 nmol/l, and between 25 and 100μg (1000 and 4000 IU)/d to bring levels beyond 75 nmol/l (on average 50μg (2000 IU)/d is required for this purpose (114)(115)(116)(117)(118)(119)(120)(121)(122)(123) ). In the present study of Crohn's disease patients, we found that 50μg (2000 IU)/d increased mean 25(OH)D levels to 91·6 (95% CI 75·5, 107·6) nmol/l over winter months, which was significantly higher than levels in the placebo group 40·4 (95% CI 30·4, 50·4) nmol/l (P < 0·001) (34) .…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, it is more readily accepted that humans are different from rats, as a species as well as in terms of weight for determining treatment doses, and that rickets prevention is not the only vitamin D action to be taken into account. The daily requirement does of course depend on what the optimal target 25-OH-D serum level is considered to be: for a 25-OH-D serum level of 50 nmol/liter, 800-1000 IU/day of vitamin D appears sufficient, but to bring most people above the 75 nmol/liter level, a dosage of between 1000 and 4000 IU/day (depending on the individual, but on average 2000 IU/day) is required [Heaney et al 2003a[Heaney et al , 2009Grant and Holick, 2005;Hollis, 2005;BischoffFerrari et al 2006BischoffFerrari et al , 2009bBischoffFerrari et al , 2012Vieth, 2006;Hall et al 2010;Schwalfenberg et al 2010;Whiting and Calvo, 2010;Cashman et al 2011;Garrett-Mayer et al 2012;Holick, 2011Holick, , 2012. However, vitamin D intake via (unfortified) food is very marginal in normal Western diets, even in those considered well balanced, and generally provides less than 100-200 IU/day, rarely reaching little more than 400 IU/day with fortified food [Calvo et al 2004;Moore et al 2005;Välimäki et al 2007;O'Donnell et al 2008;Vatanparast et al 2010;von Geldern and Mowry, 2012].…”
Section: Vitamin D Requirements and Insufficiencymentioning
confidence: 99%
“…Vitamin D supplementation for one year in both African-Americans and Caucasians in one study corrected the serum 25(OH)D discrepancy (24.1 ng/ml versus 37.2 ng/ml) after just two months of treatment, reaching a final 67.7 ng/ml and 67.3 ng/ml at one year, respectively. [2] Furthermore, a significantly higher prevalence of vitamin D deficiency was found in patients undergoing revision TJA for PJI compared to both primary TJA and aseptic loosening revision groups, with 13.29 ng/ml versus 20.52 ng/ml, respectively. [9] Interestingly, serum 25(OH)D shows an inverse relationship with C-reactive protein, although the significance of this relationship is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Many experts believe 30 ng/mL 25(OH)D reflects a minimum threshold for both skeletal and non-skeletal benefits, with an optimal range between 36 and 40 ng/ml. [2][3][4][20][21][22] The Endocrine Society recommends 1500-2000 IU D3 daily to meet these goals, and 50,000 IU D2 or D3 weekly for 8 weeks is recommended when deficiency is identified. [10] Surgical site infections (SSIs) in the setting of TJA can have catastrophic consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation